1987
DOI: 10.1182/blood.v69.2.460.460
|View full text |Cite
|
Sign up to set email alerts
|

Fibrinolysis in pregnancy: a study of plasminogen activator inhibitors

Abstract: During pregnancy the plasma concentration of two different inhibitors of plasminogen activators (PAIs) increases. The only one found in the plasma of nonpregnant women (PAI1) is immunologically related to a PAI of endothelial cells; its plasma activity, as deduced from the inhibition of single-chain tissue-type plasminogen activator (t-PA), increased from 3.4 +/- 2.3 U/mL (mean +/- 95% confidence limits) in the plasma of nonpregnant women to 29 +/- 7 U/mL at term, and its antigen level, measured by a radioimmu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
31
2
3

Year Published

1992
1992
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 300 publications
(38 citation statements)
references
References 34 publications
2
31
2
3
Order By: Relevance
“…Bonnar et al (1971) reported that overall plasma fibrinolytic activity was decreased and that this was accompanied by an increase of an inhibitor of urokinase-induced lysis in subjects with the disorder; Chmielewska et al (1983) reported an increase in fast acting inhibitor activity against t-PA in plasma from women with pre-eclampsia. It is now known that in pregnancy two distinct inhibitors of plasminogen activator (PAI-1 and PAI-2) exist in circulating blood (Kruithof et al 1987;Booth et al 1988b;Reith et al 1989). PAI-1 is present in nonpregnant individuals in significant quantities in both plasma and platelets (Booth et al 1988a) and plasma levels are altered in a variety of disease states whereas platelet levels tend not to vary (Simpson etal.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bonnar et al (1971) reported that overall plasma fibrinolytic activity was decreased and that this was accompanied by an increase of an inhibitor of urokinase-induced lysis in subjects with the disorder; Chmielewska et al (1983) reported an increase in fast acting inhibitor activity against t-PA in plasma from women with pre-eclampsia. It is now known that in pregnancy two distinct inhibitors of plasminogen activator (PAI-1 and PAI-2) exist in circulating blood (Kruithof et al 1987;Booth et al 1988b;Reith et al 1989). PAI-1 is present in nonpregnant individuals in significant quantities in both plasma and platelets (Booth et al 1988a) and plasma levels are altered in a variety of disease states whereas platelet levels tend not to vary (Simpson etal.…”
Section: Discussionmentioning
confidence: 99%
“…plasma, while PAI-1 normally circulates at about 20 ng/ml (Booth et al 1988a). The profile of these inhibitors in normal pregnancy has been established (Kruithof et al 1987;Booth et al 1988b). In normal pregnancy, levels of both inhibitors in plasma rise, PAI-1 to maximum levels of over 100 ng/ml and PAI-2 to 200 ng/ml at 30-35 weeks gestation.…”
Section: Discussionmentioning
confidence: 99%
“…The most studied physiological regulator of PAI-2 gene expression in macrophages is bacterial endotoxin, lipopolysaccharide (LPS), which induces PAI-2 mRNA and protein in both primary human monocytes and human monocyte-like cell lines [17][18][19][20][21]. Endotoxin is an archetypal inflammatory mediator and it is the actions of this compound on macrophages that induces the symptoms of toxic shock in septicemia: fever, hypotension, disseminated intravascular coagulation (DIC), and hypoxia.…”
Section: Introductionmentioning
confidence: 99%
“…One of the most physiologically striking observations for PAI-2 concerns its association with pregnancy. Plasma levels of PAI-2 increase impressively during the third trimester of pregnancy (up to 250 ngAEmL )1 ) and are maintained at these levels for up to 1 week postpartum and then rapidly decline [10]. The tissue source of plasma PAI-2 is the placenta itself.…”
Section: Expression Pattern Of Pai-2 and Its Role In Pregnancymentioning
confidence: 99%
“…General biology of PAI-2 PAI-2 was defined as a placental tissue-derived uPA inhibitor over three decades ago [8], which was subsequently verified by others [9,10]. Human PAI-2 consists of a single chain protein of 415 amino acids encoded by a 1900 bp PAI-2 transcript and is highly homologous with mouse and rat PAI-2.…”
Section: Introductionmentioning
confidence: 99%